Synthesis, Characterization, and Interaction with Biomolecules of Platinum(II) Complexes with Shikimic Acid-Based Ligands. (10th February 2013) - Peng, Yan; Zhang, Min-Min; Chen, Zhen-Feng; Hu, Kun; Liu, Yan-Cheng; Chen, Xia; Liang, Hong
Abstract : Starting from the active ingredient shikimic acid (SA) of traditional Chinese medicine and NH2 (CH2 ) n OH, (n = 2 –6), we have synthesized a series of new water-soluble Pt(II) complexes PtL a–e Cl2, where L a–e are chelating diamine ligands with carbon chain covalently attached to SA (L a–e = SA-NH(CH2 ) n NHCH2 CH2 NH2 ; L a, n = 2 ; L b, n = 3 ; L c, n = 4 ; L d, n = 5 ; L e, n = 6 ). The results of the elemental analysis, LC-MS, capillary electrophoresis, and 1 H, 13 C NMR indicated that there was only one product (isomer) formed under the present experimental conditions, in which the coordinate mode of PtL a–e Cl2 was two-amine bidentate. Their in vitro cytotoxic activities were evaluated by MTT method, where these compounds only exhibited low cytotoxicity towards BEL7404, which should correlate their low lipophilicity. The interactions of the five Pt(II) complexes with DNA were investigated by agarose gel electrophoresis, which suggests that the Pt(II) complexes could induce DNA alteration. We also studied the interactions of the Pt(II) complexes with 5 ′ -GMP with ESI-MS and 1 H NMR and found that PtL b Cl2, PtL c Cl2, and PtL d Cl2 could react with 5 ′ -GMP to form mono-GMP and bis-GMP adducts. Furthermore, the cell-cycle analysis revealed that PtL b Cl2, PtL c Cl2 cause cell G2 -phase arrest after incubation for 72 h. Overall, these water-soluble Pt(II) complexes interact with DNA mainly through covalent binding, which blocks the DNA synthesis and replication and thus induces cytotoxicity that weakens as the length of carbon chain increases.